TRANSMISSIBILITY writing aesthetic history - Emerling, Jae (London : ROUTLEDGE, 2023)
This book examines transmissibility to remind us why the vitality and epistemic significance of an artwork is anachronistic and futural. Transmissibility: Writing Aesthetic History performs a transdisciplinary philosophy of aesthetic history via the work of Gilles Deleuze and Flix Guattari, Cy Twombly, Marina Abramovi, Paul Celan, Cecil Taylor, Italo Calvino, Candida Hfer, and others by focusing on theartistic and historiographic labor that differentiates artworks from other modes of creation.
Keywords: Aesthetics; ART / History / General; PHOTOGRAPHY / Criticism